Clinical characteristics and quality care indicators of pediatric stroke in a referral center of Colombia: eleven-year experience (pediastroke) - Valencia-Cifuentes, Valeria; Llanos-Leyton, Natalia; Gómez-Ayala, Maria Camila; Ariza-Insignares, Camila; Rivillas, Julian Alejandro; Granados-Sánchez, Ana María; Márquez, Juan Camilo; Galvis-Blanco, Laura; Cruz-Zamorano, Santiago; Gómez-Castro, Juan Fernando; Lasso, Rubén Eduardo; Rámirez-Muñoz, Luis Miguel; et al. (Frontiers in Neurology, 2024)
ObjectiveThis study aims to describe clinical variables and quality care indicators in pediatric stroke management at a high-complexity pediatric care center in Latin America.MethodsRetrospective study of patients with stroke, aged 2–18 years from 2011 to 2021. The principal outcomes were the mRs and mortality. Differences between groups were assessed using Fisher’s exact test and the Mann–Whitney U test. We used logistic regression to explore the association between characteristics reported as relevant in literature and mortality.ResultsOne hundred thirty six patients included, with a median age of 11 years, 54% were male. 47% were hemorrhagic strokes, followed by ischemic strokes at 39%. One-third of the cases presented in hospital. 51% of the patients had no prior medical history. The most common symptoms were altered consciousness, headache, and hemiparesis. The median door-to-image time was 123 min. The most frequent etiologies in ischemic stroke were arteriopathies and cardiac pathology, while vascular malformation and coagulopathies were predominant in hemorrhagic stroke. No patient received reperfusion therapy. At discharge, 48% of patients had a favorable mRs. The mortality rate was 21%. Patients with in-hospital stroke have approximately 7.37 times the odds of dying compared to those with out-of-hospital stroke. Patients with hemorrhagic stroke have approximately 7.46 times the odds of dying compared to those with ischemic stroke.ConclusionSignificant gaps exist in the epidemiology and quality indicators of pediatric stroke care compared to adult protocols. Implementing a “Pediatric code stroke” protocol and conducting prospective studies are crucial for improving pediatric stroke care and outcomes.